Pengaruh Potensi Industri Garam, Produksi Garam, dan Luas Lahan Industri Garam terhadap Pertumbuhan Ekonomi di Kabupaten Sampang - Ach Isbir Fikry Syaukany,; M.Taufiq, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Salt is one of Indonesia's strategic commodities where its use is not only for human consumption but also as industrial raw material as well as for salting and various foods. In general, salt business in Indonesia is produced by evaporating seawater on a piece of coastal land with the help of wind and sunlight as a source of evaporation energy. Salt production can be carried out by coastal communities without any special skills. This can be a job opportunity for coastal communities. Talking about salt, of course it cannot be separated from an area called Madura which has long been known as "Salt Island". The salt production center on the salt island is concentrated in three regencies, namely, Sampang, Pamekasan, and Sumenep. This study aims to analyze the effect of the amount of salt industry, salt production, and salt industry land area on economic growth. The data used in this study is secondary data for the period 2011 to 2021 time series. The analysis technique in this study is multiple linear regression using SPSS 22 analysis tool. The results of this study indicate that the number of salt industries has a positive and insignificant effect, salt production has a positive and significant effect, and the area of ​​land for the salt industry has a positive and insignificant effect on economic growth in Sampang Regency.